Framework To Address Open Management Actions In Response To Board-Endorsed IEO Recommendations. (Policy Papers; Policy Paper ;, 2020)
Based on recommendations endorsed by the Evaluation Committee of the Board (EVC), this paper proposes a framework to implement the recommendation of the Third External Evaluation of the IEO to address the backlog of open management actions included in the Management Implementation Plans (MIPs) in response to Board-endorsed IEO recommendations.